Using a scenario approach to assess for the current and future demand of immunoglobulins: An interview and literature study from The Netherlands - Langi Sasongko, Praiseldy; Kraaij, Marian; So‐Osman, Cynthia (Transfusion medicine (Oxford, England), 2022)
Objectives To explore the current and future demand of immunoglobulins globally and specifically for the Netherlands by assessing: (I) which specialties contribute to current demand, (II) new areas of medical need, (III) which transformational factors may impact demand and to what effect, by using a scenario approach. Background As immunoglobulin demand continues to increase globally, there is concern of increasing shortages and questions of whether and how future demand will continue based on medical need. Methods/Materials In line with scenario principles, a scoping review of Pubmed, Web of Science, Embase and Cochrane and grey literature was conducted. Semi‐structured interviews with subject matter experts were held. The results of the review and interviews were analysed for major themes. Results The scoping review resulted in 97 articles, 74 regarding clinical uses, and 23 regarding organisational and other themes. Fifteen clinical and non‐clinical experts were interviewed. I) Neurology, immunology, and haematology were specialties that contribute most to current demand. II) Regarding potential new areas of medical need, the literature review resulted in more indications than the interviews, for example, post‐renal transplants. III) Four groups of key transformational factors were found: factors that could increase immunoglobulin demand (e.g., EMA revisions), decrease demand (e.g., replacement products, Dutch Transfer Act 2021), factors that remain to be seen how it impacts demand (e.g., further evidence), and miscellaneous factors (e.g., supply‐related). Conclusion Having identified the specialties and relevant transformational factors that affect immunoglobulin demand, more research is needed on what clinical or organisational strategies would be effective in controlling demand in general for the Netherlands and abroad. Other blood establishments may also use a scenario approach to increase preparedness for future (un)expected developments.